Pengaruh Model Problem Based Learning Berbantuan Media Pembelajaran Interaktif Terhadap Kemampuan Berpikir Kritis Matematis - Zuli Ernita Sari; Ervina Eka Subekti; Husni Wakhyudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine whether there is an effect of the Problem based learning model assisted by Interactive Learning Media on the ability to think critically mathematically in fifth grade students of SDN Berahan Wetan, Demak. This type of research is Quantitative. The population in the study were 26 students in class V SDN Berahan Wetan. The method used is True-Experimental Design, the samples taken were 26 students who were divided into two groups, namely the control group and the experimental group using random sampling technique. The results of the analysis using the t-test. The research used was a pretest-posttest control design. Based on the results of the analysis of research data after receiving the treatment of the Problem based learning Model with the Assistance of Interactive Learning Media on Mathematical Critical Thinking, it showed an increase in fifth grade students at SDN Berahan Wetan 1 Demak. From the calculation results obtained tcount>ttable, namely 32.67 >2.16, so that Ho is rejected and Ha is accepted, meaning that the average value of students' mathematical critical thinking abilities after using the problem-based learning model assisted by interactive media is greater than the average before using problem-based learning model.